Exendin-4 promotes proliferation and differentiation of MC3T3-E1 osteoblasts by MAPKs activation. (April 2016) - Feng, Yingyu; Su, Lei; Zhong, Xing; Guohong, Wei; Xiao, Haipeng; Li, Yanbing; Xiu, Lingling
Abstract : Glucagon-like peptide-1 (GLP1) and its receptor agonist have been previously reported to play a positive role in bone metabolism in aged ovariectomized rats and insulin-resistant models. However, whether GLP1 has a direct effect on the proliferation and differentiation of osteoblasts or any cellular mechanism for this potential role is unknown. We examined the effects of the GLP1 receptor agonist exendin-4 on the proliferation, differentiation, and mineralization of mouse osteoblastic MC3T3-E1 cells. GLP1 receptor was detected in MC3T3-E1 cells by polymerase chain reaction (PCR) and Western blot assay. Cell proliferation was assessed using MTT assay, revealing that exendin-4 increased cell proliferation at effective concentrations between 10 −10 and 10 −5 M. Quantitative PCR analysis showed that exendin-4 increased the mRNA expression of the differentiation markers alkaline phosphatase (ALP), collagen-1 (COL1), osteocalcin (OC), and runt-related transcription factor 2 (RUNX2) under osteogenic conditions. Alizarin red staining confirmed that 10 −7 M exendin-4 increased osteoblast mineralization by 18.7%. Exendin-4 upregulated the phosphorylation of ERK1/2, p38, and JNK, with the peak effect at 1.5 h in the Western blot analysis. The use of selective MAPK inhibitors, namely PD98059, SB203580, and SP600125, blocked the effects of exendin-4 on kinase activation (ERK1/2, p38, and JNK), as well as cell proliferation and differentiation in MC3T3-E1 cells. These findings demonstrate that exendin-4 promotes both the proliferation and differentiation of preosteoblasts MC3T3-E1 via activation of the MAPK pathway.